The Possibilities to Use Individual and Social Resources in Case of Unemployment - ДеминАндрей Николаевич (Journal of Economic Sociology, 2010)
The paper analyzes the peculiarities of individual self-organization of unemployed. The concept of сoping behaviour, used in the paper, allows to consider concrete mechanisms of overcoming life difficulties and crises. The author works out three main forms of individual self-organization of unemployed:goal-seeking use of social network resources; effective concretization of self image, personal plans and evaluation of the current situation; shaping the context of the current situation. These forms could be the object of social support, provided through professional orientation. The author’s definition of professional orientation is given. The author makes a conclusion of that the development of the system of consultancy support for the professional career is needed.